Clusterin: a double-edged sword in cancer and neurological disorders - Sultana, Pinky; Novotny, Jiri (EXCLI journal, 2024)
Clusterin is a ubiquitously expressed glycoprotein that is involved in a whole range of biological processes. This protein is known to promote tumor survival and resistance to therapy in cancer, which contrasts sharply with its neuroprotective functions in various neurological diseases. This duality has led to recent investigations into the potential therapeutic applications of clusterin inhibition, particularly in cancer treatment. Inhibition of clusterin has been shown to be able to induce cancer cell senescence, suppress their growth and increase their sensitivity to therapy. The involvement of clusterin in the aging process makes its biological effects even more complex and offers a broad perspective for research and therapeutic exploration of various pathological conditions. This review critically examines the multiple functions of clusterin in cancer and neurological disorders and addresses the controversies surrounding its role in these areas. The assessment includes an in-depth analysis of the existing literature and examining the relationship of clusterin to fundamental aspects of cancer progression, including cell proliferation, apoptosis, metastasis, and drug resistance. In addition, the review addresses the neurobiological implications of clusterin and examines its controversial role in neuroprotection, neurodegeneration, and synaptic plasticity. Attention is also paid to the epigenetic regulation of clusterin expression. By clarifying conflicting findings and discrepancies in the literature, this review aims to provide a nuanced understanding of the molecular mechanisms underlying clusterin functions and its potential clinical implications in both cancer and neurodisorders. See also the graphical abstract(Fig. 1).
Keywords: cellular senescence; clusterin; cancer; aging